Es hora de salir - Testa, Fulvio; Cardenoso, Concha (Barcelona : Timun Mas, 1993)
A little boy's imagination creates an exciting adventure as he takes a bath.
First published in Great Britain by Andersen Press Ltd.
Titulo original: Time to get out.
Keywords: Imagination -- Fiction; Baths -- Fiction; Spanish language materials -- Juvenile fiction; Picture books